Malecite-Passamaquoddy materials, Phillips Fund Collection - Campana, Mark; Knecht, Laura; LeSourd, Philip S.; Ng, Eve; Paul, Peter Lewis, 1902-1989; Smith, Nicholas N. (1975)
The Malecite-Passamaquoddy materials in the Phillips Fund collection consist of 6 items. Materials in this collection are listed alphabetically by last name of author. See materials listed under Campana, Knecht, LeSourd, Ng, and Smith.